2011
DOI: 10.1016/j.pain.2011.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal and anatomical analyses of P2X receptor-mediated neuronal and glial processing of sensory signals in the rat dorsal horn

Abstract: Extracellularly released adenosine triphosphate (ATP) modulates sensory signaling in the spinal cord. We analyzed the spatiotemporal profiles of P2X receptor-mediated neuronal and glial processing of sensory signals and the distribution of P2X receptor subunits in the rat dorsal horn. Voltage imaging of spinal cord slices revealed that extracellularly applied ATP (5-500 μM), which was degraded to adenosine and acting on P1 receptors, inhibited depolarizing signals and that it also enhanced long-lasting slow de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 73 publications
2
23
0
Order By: Relevance
“…In the present study, we found that P2X7Rs were also located mainly in microglia, to a lesser extent in astrocytes in the spinal dorsal horn after SMIR. This is also in line with previous studies that apart from microglia, P2X7Rs are expressed in astrocytes of the cerebral cortex (Oliveira et al, 2011) and of the spinal dorsal horn (Aoyama et al, 2011). P2X7Rs play a pivotal role in the cross-talk between microglia and neurons (Sperlagh et al, 2006).…”
Section: The Genesis Of Pathological Pain Without Nerve Injurysupporting
confidence: 93%
“…In the present study, we found that P2X7Rs were also located mainly in microglia, to a lesser extent in astrocytes in the spinal dorsal horn after SMIR. This is also in line with previous studies that apart from microglia, P2X7Rs are expressed in astrocytes of the cerebral cortex (Oliveira et al, 2011) and of the spinal dorsal horn (Aoyama et al, 2011). P2X7Rs play a pivotal role in the cross-talk between microglia and neurons (Sperlagh et al, 2006).…”
Section: The Genesis Of Pathological Pain Without Nerve Injurysupporting
confidence: 93%
“…Attempting to clarify the matter, Aoyama et al recently reported a systematic analysis of the distribution of all seven P2X receptors in the dorsal horn and compared their findings to earlier reports [46]. From this they concluded that P2X1 and P2X3 receptor subunits are densely distributed mainly in laminae I and II of the dorsal horn and are presumably expressed at the afferent nerve terminals [38].…”
Section: Purinergic Receptor Expression On Nociceptive Neuronsmentioning
confidence: 99%
“…VSD imaging techniques have been applied, e.g., to the sensory system of the spinal cord [17][19] as well as to the respiratory central pattern generator of the brainstem [20][23]. Also, mathematical methods to more efficiently detect neural activities from spatio-temporal data obtained by VSD imaging have been developed [23], [24].…”
Section: Discussionmentioning
confidence: 99%
“…The procedures using animals were done in accordance with the NIH Guide for the Care and Use of Laboratory Animals and were approved by the Animal Research Committee of Shimane University School of Medicine. The histological technique of NeuN staining has been described elsewhere [17]. Briefly, neonatal rats (Wistar, 4–5 day-old, n = 4) were deeply anesthetized by intraperitoneal injection of chloral hydrate (350 mg/kg), perfused transcardially with saline, and fixed with 4% paraformaldehyde in 0.1 M phosphate buffer (pH 7.3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation